PENERAPAN PEMBERIAN IZIN USAHA BERBASIS RISIKO TERHADAP PELAKU USAHA MIKRO KECIL DAN MENENGAH DI DESA KEMBANG KERANG DAYA (STUDI KASUS DI DINAS PMPTSP KAB. LOMBOK TIMUR: Implementation Of Risk-Based Business License Granting To Small And Medium Micro Enterprises In The Kembang Kerang Daya Village (Case Study At The Pmptsp Department Of East Lombok Regency) - Ningsih, Kurnia (Fakultas Hukum Universitas Gunung Rinjani, 2023)
The purpose of this study is to find out How is the implementation of granting of risk-based business permits according to Government Regulation Number 5 of 2021 and what are the inhibiting factors for micro, small and medium businesses actors in Kembang Karang Daya village in processing their business permits at the one-stop investment and integrated services service in East Lombok Regency. The aim of this research is to find out how permits are implemented for micro, small and medium enterprises and what factors inhibit micro, small and medium enterprises in obtaining their business permits. This type of research is empirical normative legal research which includes interviews and direct observation from actual community actors, and normative law is a process of finding legal rules, legal principles and legal doctrines to answer the legal issues faced. Based on the result of the author’s research, the administration of business licensing from the applicant stage to the issuance of the permits is carried out electronically through the OSS-RBA (Online Single Submission – Risk Based Approach) system. and Public ignorance about risk-based business permits, lack of information and socialization from the government about risk-based business permits and low computer literacy are factors that hinder business actors in the Kembang kerang Daya Village in processing their business permits.